Who Should Merge with Whom? Financial Benefits and Costs from Mergers and Acquisitions - Christian Koziol; Markus Theis (Kredit und Kapital, 2011)
Who Should Merge with Whom? Financial Benefits and Costs from Mergers and Acquisitions Mergers and acquisitions are prominent forms of transactions that combine two firms in a way that one unit with a new asset and a new liability side arises. Since both the equity and the debt positions of the merging entities are affected by such a deal, it is not clear whether positive synergies are equivalent to an improvement of the acquirer equity holders' position, who initiate the takeover decision. We introduce a frictionless, continuous-time model to compute the financial costs for the acquirers' equity value, when carrying out a zerosynergy takeover. This allows us to identify the characteristics of potential target companies that are especially well-suited to reduce these financial costs (and thus make a deal worthwhile for given synergies). We find that firms should consider targets having about the same business risks and relatively low debt ratios. While targets are supposed to be small in mergers, they can also be comparably large in debt financed acquisitions. Empirical observations support the relevance of the wealth effects of the debt position suggested by the model and additionally reveal that the acquirers' debt position is affected in different directions depending on whether a merger or an acquisition takes place. (JEL G32, G34) – – Wer sollte mit wem fusionieren? Finanzielle Synergien und Kosten aus Mergers und Akquisitionen Mergers und Akquisitionen sind weitreichende Transaktionen, die zwei Unternehmen zu einer Einheit mit neuen Aktiva und neuen Passiva verbinden. Da sowohl die Eigenkapital- als auch die Fremdkapitalpositionen beider fusionierender Unternehmen betroffen sind, müssen positive operative Synergien nicht gleichbedeutend mit einem Vermögenszuwachs für die Eigenkapitalgeber des übernehmenden Unternehmens sein, welche eine Transaktion üblicherweise initiieren. Um finanzielle Kosten ihrer Position frei von Synergien darzustellen, führen wir ein zeitstetiges Modell in einer friktionslosen Umgebung ein. Auf diese Weise können wir Charakteristika von potenziellen Zielunternehmen identifizieren, die finanzielle Kosten minimieren (und bei gegebenen operativen Synergien somit zu lohnenswerten Transaktionen führen). Zielunternehmen sollten demnach gering verschuldet und einem ähnlichen Geschäftsrisiko ausgesetzt sein wie das übernehmende Unternehmen. Während darüber hinaus verhältnismäßig kleine Zielunternehmen in Mergers von Vorteil sind, dürfen sie in fremdfinanzierten Akquisitionen auch deutlich größer sein als das akquirierende Unternehmen. Empirische Beobachtungen bestätigen die modelltheoretisch abgeleitete Bedeutung der Fremdkapital-Vermögenseffekte und enthüllen darüber hinaus, dass die Fremdkapitalposition eines übernehmenden Unternehmens in Mergers und Akquisitionen gegenläufigen Effekten ausgesetzt ist.
Keywords: G32; G34; 330